2022
DOI: 10.3390/cancers14061419
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide-Modulated Changes in Metabolism, Glycosylation Profile and Migration of Metastatic Melanoma Cells

Abstract: An effective therapy for advanced melanoma, a skin cancer with the highest mortality, has not yet been developed. The endocannabinoid system is considered to be an attractive target for cancer treatment. The use of endocannabinoids, such as anandamide (AEA), is considered to be much greater than as a palliative agent. Thus, we checked its influence on various signaling pathways in melanoma cells. Our investigation was performed on four commercial cell lines derived from different progression stages (radial WM3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…We could also rule out the possibility that anandamide was simply toxic to the cells, as we saw no increase in 7-AAD positive cells ( Figure 1A ). This was an important control experiment, as others have reported significant cell death with similar concentrations in keratinocytes [10 μM, ( 43 )], melanoma cells [13.5 μM, ( 44 ); >5 μM, ( 45 )], sebocytes [>10 μM, ( 46 )], and murine DCs [>5 μM, ( 47 )].…”
Section: Discussionmentioning
confidence: 99%
“…We could also rule out the possibility that anandamide was simply toxic to the cells, as we saw no increase in 7-AAD positive cells ( Figure 1A ). This was an important control experiment, as others have reported significant cell death with similar concentrations in keratinocytes [10 μM, ( 43 )], melanoma cells [13.5 μM, ( 44 ); >5 μM, ( 45 )], sebocytes [>10 μM, ( 46 )], and murine DCs [>5 μM, ( 47 )].…”
Section: Discussionmentioning
confidence: 99%
“…ROS (Reactive Oxygen Species) assay. The methodology was adapted from previous work [27]. Media from 24 h cultures grown in 96-well plates were discarded, and the cells were gently washed with PBS.…”
Section: Metabolic Activity Tests-mtt Crystal Violet and Ros Assaysmentioning
confidence: 99%
“…Moreover, evidence regarding cannabinoid ability to affect the Wnt pathway, thus altering the epithelial-mesenchymal transition and chemoresistance, has been shown in different tumor types and has been associated with a reduction of β-catenin target genes and mesenchymal markers [ 9 ]. Focusing on N-arachidonoyl-ethanolamine, anandamide (AEA), the cannabinoid used in this study, previous in vitro results demonstrated its role in the inhibition of breast tumor-induced angiogenesis [ 10 ] and the alteration of metabolism, glycosylation profile, and migration of metastatic melanoma cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%